Two-step simulations of reaction systems by minimal ones - Salomaa Arto (2015)
Reaction systems were introduced by Ehrenfeucht and Rozenberg with biochemical applications in mind. The model is suitable for the study of subset functions, that is, functions from the set of all subsets of a finite set into itself. In this study the number of resources of a reaction system is essential for questions concerning generative capacity. While all functions (with a couple of trivial exceptions) from the set of subsets of a finite set S into itself can be defined if the number of resources is unrestricted, only a specific subclass of such functions is defined by minimal reaction systems, that is, the number of resources is smallest possible. On the other hand, minimal reaction systems constitute a very elegant model. In this paper we simulate arbitrary reaction systems by minimal ones in two derivation steps. Various techniques for doing this consist of taking names of reactions or names of subsets as elements of the background set. In this way also subset functions not at all definable by reaction systems can be generated. We follow the original definition of reaction systems, where both reactant and inhibitor sets are assumed to be nonempty.
Keywords: Természettudományok; Számítás- és információtudomány